Spatial variability of soil water content and mechanical resistance of Brazilian ferralsol - Junior, V. V.; Carvalho, M. P.; Dafonte, J.; Freddi, O. S.; Vazquez, E. V.; Ingaramo, O. E. (Elsevier B.V., 2006)
The spatial variability of mechanical resistance to penetration (PR) and gravimetric moisture (GM) was studied at a depth of 0-0.40 m, in a ferralsol cropped with corn, and under conventional tillage in llha Solteira, Brazil (latitude 20 degrees 17'S, and longitude 52 degrees 25'W). The purpose of this study was to analyse and to try explaining the spatial variability of the mentioned soil physical properties using geostatistics. Soil data was collected at points arranged on the nodes of a mesh with 97 points. Geostatistics was used to analyse the spatial variability of PR and GM at four depths: 0-0. 1, 0.1-0.2, 0.2-0.3 and 0.3-0.4 m. PR showed a higher variability of data, with coefficients of variation of 52.39, 30.54, 16.91, and 15.18%, from the surface layers to the deepest layers. The values of the coefficients of variation for GM were lower: 9.99, 5.13, 5.59, and 5.69%. Correlation between GM and PR for the same soil layers was low. Penetration resistance showed spatial structure only in the 0.30-0.40 m layer, while gravimetric moisture showed spatial structure at all depths except for 0-0. 10 m. All the models of fitted semivariograms were spherical and exponential, with ranges of 10-80 m. Data for the variable 'GM' in the 0.20-0.30 and 0.30-0.40 m layers revealed a trend in data attributed to the occurrence of subsurface water flow. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: geostatistics; spatial variability; soil moisture; penetration resistance of soil